2x+6=-1x+5

Simple and best practice solution for 2x+6=-1x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=-1x+5 equation:



2x+6=-1x+5
We move all terms to the left:
2x+6-(-1x+5)=0
We get rid of parentheses
2x+1x-5+6=0
We add all the numbers together, and all the variables
3x+1=0
We move all terms containing x to the left, all other terms to the right
3x=-1
x=-1/3
x=-1/3

See similar equations:

| 12=16k/3 | | 4x=2=14 | | -6x-6+x=9 | | -7(x+9)=(x-5)-14x | | 4(x+15)=9 | | 3(5x-2)=-3(x+16) | | -3x+21+2=20 | | 3h/10-17=527/40 | | 32-1(3c+4)=2(c+5)+c | | 5x-2+3=x | | 4(x+3)=-2(x-5) | | 5y−4=36 | | 11b–20=2+10b–3 | | -5x+7=-2(x-4) | | -x+1=x+21 | | 3x-10(2x-1)=44 | | y+3y=96= | | 4y-12+3y+18=27 | | -2/3=-4/3(s-1/3) | | y+3y=86 | | 2-(3-2(x+1)=3x+2(x-(3+2x) | | 3x+(x+42)=90 | | 8c-15=1 | | 1/4(4r−8)=r−2 | | 7x+8x=36 | | 9/m+7=3 | | x+7/3-4=x-5 | | 3.6=8.1-0.5x | | 1/2(15+7d)=d/4 | | -1=4/7t | | 4z+10=16 | | 4(c-12+19=-89 |

Equations solver categories